The Ultra Ganges Mission Activities and Impact on the Press in Pre-Modern China - Chen, Changyu; Wang, Hai (Integrated Journal for Research in Arts and Humanities, 2024)
Before the Opium War, Protestant missionaries to China took the Ultra Ganges Mission as a link, and carried out a series of literal missionary activities, and set up missionary stations and printing presses, church schools, and Chinese and foreign-language newspapers and magazines in the South Seas and in China's Canton and Macao, etc. The newspapers founded under the guidance and support of the Ultra Ganges Mission introduced the Western newspaper concepts and newspaper editing and printing techniques into China, cultivated the early Chinese newspaper group, and laid the material and human resource foundation for the Chinese to imitate foreign newspapers and run their own newspapers after the Opium War. By analyzing the historical facts about the establishment of modern Chinese and foreign newspapers and magazines by the Ultra Ganges Mission, this essay demonstrates how the foreign newspapers in China in the first half of the 19th century promoted and influenced the emergence and development of the modern newspaper industry in China.